1967
DOI: 10.1002/pol.1967.150050901
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐opening polymerization of unsaturated alicyclic compounds

Abstract: synopsisThe ring-opening polymerizations of cyclooctene, cyclododecene, 1,5cyclooctadiene, 1,5,9-~yclododecatriene, 3-methylcyclooctene, and 3-phenylcyclooctene have been carried out by using a twycomponent catalyst system composed of ethylaluminum dichloride and tungsten hexachloride. NMR and infrared analyses of the respective polymers indicate structures which are consistent with a ring-cleavage mode of propagation. No evidence for double-bond shifts or transannular reactions during the polymerizations of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(41 citation statements)
references
References 9 publications
0
33
0
3
Order By: Relevance
“…1) 1) . The reverse reaction of the ROMP is called back biting and proceeds intramolecularly as a degradation process generating rings and shorter chains.…”
Section: Introductionmentioning
confidence: 98%
“…1) 1) . The reverse reaction of the ROMP is called back biting and proceeds intramolecularly as a degradation process generating rings and shorter chains.…”
Section: Introductionmentioning
confidence: 98%
“…However, the presence of trace amounts of acyclic olefins explains why the high molecular weight fractions observed are acyclic hydrocarbons, obtained by cross metathesis, rather than cyclic, polymers [7]. Cyclic alkenes, except cyclohexene, from C 4 to C 12 , yield polyalkenes which vary from amorphous elastomers to crystalline materials.…”
Section: Cyclic Olefinsmentioning
confidence: 96%
“…The dependence of the stereospecificity on the nature of the organometallic compound for WCl 6 based catalytic systems has been studied by Gunther, Haas et al [283,284]. Calderon et al [285] have found that the catalytic activity at room temperature increases in the order AlEtCl z > AlEtzCI > AlEt3 for WCl 6 based systems.…”
Section: Ring Opening Polymerization Of Cycloolefinsmentioning
confidence: 97%